The concept of figurative subjectivity is evident in the works of the innate Iraqi sculptor Moneim Furat (Journal of the College of Basic Education, 2022)
In this research, the researcher was concerned with studying and discovering the manifestation of the pictorial subjectivity in the works of the innate Iraqi sculptor Moneim Furat. The research consisted of four chapters. The chapter also included the clarification of the axes (the concept, the self, the innate, the innate art) in terms of language, terminology, and philosophy. The second chapter included two topics: the self, and the psychological life of Monem Furat.